ANALYSIS OF THE INFLUENCE OF THE LOVE OF MONEY, LIFESTYLE AND USE OF SHOPEE PAYLATER ON STUDENTS' PERSONAL FINANCIAL MANAGEMENT - Yanti Susanti; Nesya Angelita (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to determine the influence of the love of money, lifestyle and use of Shopee Paylater on students' personal financial management. The population used is students of the digital business study program at Yatsi Madani University class of 2023 who use Shopee Paylater. The sample consisted of 105 respondents, which were taken by purposive sampling method. The hypothesis testing technique in this study uses statistical analysis consisting of multiple linear regression, F test, t-test and determination coefficient (R2) using the help of the SPSS 25 system. The research data is sourced from primary data and is taken by distributing questionnaires. The results of the study show that there is a relationship between independent variables, namely the use of Shopee Paylater, and the dependent variable of students' personal financial management. Based on the results of the study, it can be seen that Love of Money (X1) and Lifestyle (X2) have a significant influence on students' personal financial resources. However, in the variable Use of Shopee Paylater (X3), there is no effect on the student's personal financial management. The conclusion in this study confirms that some students have a positive view of the love of money or have a desire to follow a lifestyle, on the contrary, the use of Shopee Paylater has been proven to have no positive influence on students' personal financial management. Because the ease of access to credit has not fully encouraged improved discipline or better financial planning among students.